EFFECTIVENESS OF EPLEY’S MANEUVER IN POSTERIOR CANAL BENIGN PAROXYSMAL POSITIONAL VERTIGO: A PROSPECTIVE OBSERVATIONAL STUDY - Sharma, Nitin; Bali, Apurva; Anamika, Anamika; Sharma, Pritosh (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the present study was to determine the effectiveness of Epley’s maneuver in curing posterior canal benign paroxysmal positional vertigo (BPPV). Methods: This was a single-center, hospital-based, prospective observational study involving a total of 51 patients diagnosed with BPPV. The diagnosis of BPPV was confirmed by Dix–Hallpike’s maneuver (DHM). The patients of BPPV were treated using Epley’s maneuver. The patients were followed on the 4th, 10th, 30th, and 180th days after the initial consultation. The response to DHM was recorded on each follow-up visit. Results: Among the enrolled 51 participants, 47 did not have any complaints related to giddiness post treatment. Thus, the effectiveness of Epley’s maneuver in treating posterior semicircular canal BPPV at 6 months was 92.16%. Overall, 5 participants (10.6%) who were cured on the first follow-up visit had a recurrence of BPPV at the 1-month follow-up visit. As the duration of follow-up increased, the quality-of-life score decreased, indicating that patients felt better or relieved from symptoms with time. On the follow-up visits on day 4, day 10, 1 month, and 6 months after Epley’s maneuver, it was 43.1%, 72.5%, 88.2%, and 92.2%, respectively, for those who had a negative response to DHM. Conclusion: Epley’s maneuver is an effective treatment modality for patients diagnosed with posterior semicircular canal BPPV and shows a significant improvement in quality of life for such patients with low recurrence rates.